Regional ice flow piracy following the collapse of Midgaard Glacier in Southeast Greenland - Flora Huiban; Romain Millan; Kristian Kjellerup Kjeldsen; Camilla S. Andresen; Mads Dømgaard; Amaury Dehecq; Stephen Brunt; Shfaqat Abbas Khan; Jérémie Mouginot; Anders Anker Bjørk (Nature Communications)
Abstract Southeast Greenland contributes significantly to global sea level rise, with mass loss having increased by about 600% over the past 30 years due to enhanced melt and dynamic instabilities of marine-terminating glaciers. Accurate modelling of glacier dynamics is crucial to minimise uncertainties in predictions of future sea level rise, necessitating detailed reconstructions of long-term glacial histories. One key complexity in these models that is not well understood or documented is ice flow piracy, where ice is redirected between catchment basins, significantly influencing regional glacier dynamics and mass balance. Here, we document and characterise the collapse of Midgaard Glacier in Southeast Greenland using a multi-data approach, providing a 90-year record of the area’s complex glacial history. Initiated over 80 years ago, this collapse triggered catchment-scale dynamic changes in several neighbouring glaciers, impacting local glacial stability throughout the 20th century and into the present. Our analysis reveals that catchment-scale ice flow piracy can cause substantial disturbances in mass balance evolution and catchment reconfigurations, independent of climatic conditions. These findings underscore the importance of understanding long-term changes in complex glacier systems to make accurate predictions of future glacial mass loss and associated sea-level rise.